2020
DOI: 10.3390/nu13010004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Milk-Based Infant Formula Fortified with PUFAs on Lipid Profile, Growth and Micronutrient Status of Young Children: A Randomized Double-Blind Clinical Trial

Abstract: Background: Polyunsaturated fatty acids (PUFAs) are essential to child growth and development. Objective: To assess the effect of PUFAs-fortified infant formula on lipid profile, growth and micronutrient status in children 12 to 30 months old. Methods: This study is a double-blind randomized controlled clinical trial. Two study groups were assessed: (a) milk-based infant formula with micronutrients and PUFAs (PUFAs) and (b) milk-based infant formula with micronutrients, no PUFAs added (Non-PUFAs). Children rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A double-blind, randomized clinical research study showed that children who received infant formula enhanced with micronutrients and PUFAs had better lipid profiles compared to children who only got micronutrientfortified formula. Infants in both groups improved their length/height-for-age Z-score (16). Additionally, the findings was consistent with another study reporting that supplementing stunted children under age five with 350 -500 mg of omega-3 fatty acid may help them grow taller (18).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A double-blind, randomized clinical research study showed that children who received infant formula enhanced with micronutrients and PUFAs had better lipid profiles compared to children who only got micronutrientfortified formula. Infants in both groups improved their length/height-for-age Z-score (16). Additionally, the findings was consistent with another study reporting that supplementing stunted children under age five with 350 -500 mg of omega-3 fatty acid may help them grow taller (18).…”
Section: Discussionsupporting
confidence: 88%
“…Thirteen out of thirty-five studies discovered the beneficial impact of supplementing omega-6 or omega-3 FA towards children's growth whether they are healthy or malnourished children. The supplementation of omega-3 or omega-6 FA is associated with increased height or length and weight gain amongst children who are short stature or have normal health (10,(15)(16)(17)(18)(19)(20)(21). In contrast, two studies reported no significant effects of PUFA supplementation on body weight (22,23).…”
Section: Growthmentioning
confidence: 99%
“…Finally, a randomized controlled trial among 12-30-month-old Mexican infants demonstrated that supplementation of formula with ~1240 mg LA + 156 mg ALA + 33 mg DHA/day for 4 months did not significantly improve health outcomes (all p > 0.05) despite significantly increasing ALA and DHA serum levels (both p < 0.05) [71]. This study may not have seen an association because relative to other studies discussed [38], the amount of DHA supplemented was quite low [71]. Despite these limitations, these studies demonstrate that n-3 PUFAs may not affect growth outcomes in childhood as much as other FAs, notably n-6 PUFAs.…”
Section: Associations Between Pufas and Growth Outcomes In Childrenmentioning
confidence: 97%
“…The lack of an effect in this study could be due to the fact that these preterm infants had a wide range of birthweights and gestational ages, which could make it more difficult to detect the effect of supplementation, or the supplementation was not long enough to effect short-term growth or adiposity [73]. Finally, a randomized controlled trial among 12-30-month-old Mexican infants demonstrated that supplementation of formula with ~1240 mg LA + 156 mg ALA + 33 mg DHA/day for 4 months did not significantly improve health outcomes (all p > 0.05) despite significantly increasing ALA and DHA serum levels (both p < 0.05) [71]. This study may not have seen an association because relative to other studies discussed [38], the amount of DHA supplemented was quite low [71].…”
Section: Associations Between Pufas and Growth Outcomes In Childrenmentioning
confidence: 98%
“…There are also a growing number of published clinical studies showing value with beneficial short-term effects of YCFs ( Table 2 ). These double-blind, randomized, controlled, clinical trials were of strong study designs, although there were a limited number and heterogeneity in populations, formulations, duration, serving sizes, and ages [ 35 , 36 , 37 , 38 ]. All but one clinical study demonstrated beneficial effects of primary outcomes that ranged from nutrient status with improved lipid profile, increased folate levels [ 36 ], and preserved iron status [ 35 ] to body composition with a lower percentage of body fat [ 37 ] to immune parameters with increased total blood immunoglobulin A level [ 38 ].…”
Section: Young Child Formula (Ycf)/toddler Drink Guidelinesmentioning
confidence: 99%